Key Success Factors for Digital B2B Self-Service The Case for the ICT Industry - Lundqvist, Måns; Sandén, Adam (My University, 2024)
Background and Problem: Despite increasing demand for Self-Service Technologies (SSTs) in the B2B landscape, ICT firms are yet to untap the potential for competitive advantage enabled by SSTs. An increased understanding of success factors for SSTs can help ICT players to serve customer needs more accurately. Purpose: Identify key success factors for B2B self-service tools in the ICT industry. Literature Overview: As a result of reviewing literature around the topics technology adoption, information system success, and SSTs, a conceptual framework was built which highlighted 12 determinants of general SST success. These are: perceived ease of use, design, convenience, service quality, customization, subjective norm, voluntariness, result demonstrability, functionality, enjoyment, security, and assurance. Method: A qualitative approach was employed, where semi-structured interviews were conducted with users, sellers providing self-service, and third-party providers of self-service solutions. The 12 determinants of SST success identified in the conceptual framework constituted the themes which formed the basis of the interview topics and analysis of results. Findings: Subjective norm, enjoyment and assurance was rejected as determinants of SST success within the scope of B2B and ICT. Within the areas of the remaining nine determinants, key success factors were identified. First, creating the perception of ease of use is the most important success factor, where a simple user interface should be prioritized over complex features. Secondly, security of information should not be compromised for increased convenience, although the optionality of the customer regarding degree of security may be a success factor. Third, customers should be able to configure their self-service experience, although the risk of individual customers not knowing what the optimal configurations are for them must be considered. Fourth, the use of the SST should always be combined with human support to create a sense of voluntariness and high service quality. Fifth, results and KPIs of SST usage should be communicated, as it creates an increased understanding of usage benefits for customers and generates better incentive to develop the SST further for the provider. Lastly, the future of B2B self-service is expected to follow the development of B2C self-service. Followingly, increased usage of AI and IoT technologies will require human support to be more customer-oriented rather than product- and service-oriented.
Keywords: Self-Service; SST; ICT; B2B Platform; Technology Adoption; Service Quality